The Udder Side of Maritime Rights:: Bovine Tuberculosis and Federal Regulatory Power in 1920s Prince Edward Island - Jenkins, Jane (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2011)
Abstract This article traces the federal program to eradicate bovine tuberculosis during the early 20th century, the dynamics of Prince Edward Island’s two-year battle to participate, and the motivation behind the unexpected decision to test PEI cows after steadfast refusals. Rather than a progress narrative, the article reveals the rise of the regulatory state in tandem with the authority of veterinary science – wielded in order to fracture the unity of regional dissent. The establishment of PEI as a zone free of bovine tuberculosis was thus as much about politics and profit as it was about public health and progressivism.